Combination of Ant Colony Optimization with Local Triangular Kernel Clustering for Vehicle Routing Problem with Time Windows - Aina Musdholifah; Rahman Indra Kesuma (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
VRP is a common problem that occurred in logistics, including determination a route of products from the source to the destination. VRPTW is variation of VRP that use routing concepts in the serving process at the certain time interval. Recently, many methods are used to solve this optimization problem, for example ACO. LTKC-ACO was developed to improve the ACO solutions that apply LTKC to obtain a number of classes that are considered as the candidate list in ACO. Local Search is also used to avoid ACO getting stuck in the local optimum. In this study, two types of LTKC-ACO are developed that’s related to time windows parameter usage in clustering. The experimental result of 56 Solomon’s datasets showed that LTKC-ACO can improve the ACO solutions on 73,21% of datasets and can out performed then the other methods, especially on the datasets that have longer scheduling of service time.